2020
DOI: 10.2147/opth.s254504
|View full text |Cite
|
Sign up to set email alerts
|

<p>Differential miRNA Expression: Signature for Glaucoma in Pseudoexfoliation</p>

Abstract: To investigate the microRNA (miRNA) profile in patients with different stages of pseudoexfoliation (PXF). Methods: Peripheral blood of patients with PXF (naïve to medical therapy and with no systemic disease/drugs) with ocular hypertension (OHT) and pseudoexfoliation glaucoma (PXG) was evaluated in triplicate for miRNA profiling using polymerase chain reaction (PCR) arrays. Those identified in the discovery stage were validated with evaluation of serum transforming growth factor-β1 (TGF-β1) levels by ELISA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Concentration of TGFβ1 was evaluated in our previous study [ 20 ] and as expected these results are consistent with our previous results as we found in tears and AH, its expression is higher in PXG as compared to PXF or control. The MMP-9 and MMP-2 activities in serum were significantly upregulated in PXF and PXG compared to control while MMP-9 significantly downregulated in PXG when compared to PXF ( Fig 2d and 2e ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Concentration of TGFβ1 was evaluated in our previous study [ 20 ] and as expected these results are consistent with our previous results as we found in tears and AH, its expression is higher in PXG as compared to PXF or control. The MMP-9 and MMP-2 activities in serum were significantly upregulated in PXF and PXG compared to control while MMP-9 significantly downregulated in PXG when compared to PXF ( Fig 2d and 2e ).…”
Section: Resultssupporting
confidence: 92%
“…The intensity of antibody immunostaining was scored as: 0 (none), 1 (weak), 2 (moderate), and 3 (strong). Total immunostaining scores, which combined intensity and distribution of immunostaining, were ranked as low (intensity 0–1 and distribution 0–4, or intensity 2 and distribution 0–1) or high (intensity 2–3 and distribution 2–4) [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lower concentration of 5 ng/mL showed asymmetric changes with different molecules getting upregulated at different time points suggesting the pro-fibrotic activity was maximally upregulated at 10 ng/mL of TGF-β1 after 24 h of sustained exposure. Since misfolded proteins seen in pseudoexfoliation recruits the Unfolded protein response (UPR) pathway and the inflammatory cytokines, we evaluated the expression of UPR genes X-box-binding protein 1 ( XBP1 ) and Chaperon containing TCP1 subunit 4 ( CCT4 ) that we found earlier to be downregulated in patients with advanced pseudoexfoliation glaucoma [ 15 ]. Consistent with our earlier study, we found XBP1 and CCT4 to be downregulated in vitro after 48 h exposure of 10 ng/mL TGF-β1 ( Figure 3 f).…”
Section: Resultsmentioning
confidence: 99%
“…We also found decreasing tear and aqueous MMP9 activity, with increased inflammatory cytokine levels, in severe PXG eyes compared to primary glaucoma [ 14 ], suggesting that the elevated TGF levels somehow were important for molecular events that causes the disease. We also found serum levels to parallel the levels in the aqueous and tears with several key miRNA driven by TGF-β1 to be upregulated in eyes with ocular hypertension (OHT) and PXG [ 15 ]. This was also associated with downregulation of several unfolded protein response (UPR) genes, a key mechanism of abnormal ECM homeostasis in PXF.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative/nitrosative stress plays a pivotal role in POAG pathogenesis [ 12 , 15 , 39 ]; we may hypothesize that in the course of glaucoma, the pro-oxidants may induce the expression of miR-26b-5p, as reflected in this work [ 39 , 40 , 41 ]. Interestingly, hsa-miR-26b-5p has recently been involved in pseudoexfoliative glaucoma through interaction with the TGFR1 and TGR2 part of SMAD2 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%